Radical innovation in financial institution: Exploring the business process reengineering (BPR) practices and the level of its implementation in Nigeria - Ringim, Kabiru Jinjiri; Razalli, Mohd Rizal; Hasnan, Norlena (2012)
Business Process Reengineering(BPR) can radically improve operational process of an organization for superior organizational performance.The main objective of this paper is to explore the BPR practices in Nigerian financial institutions.Additionally, it also examines the level of implementation of BPR practices in these institutions.The data received from the commercial bank departments was analysed using the SPSS software.The findings show that BPR implementation was found in various operational processes in banks.In addition, the findings also indicate that the banks managers have perceived that their banks are effectively implementing BPR-related factors namely change management, process innovation, IT usage, and IT capability.The research is significant to the banks, financial institutions and entrepreneurs in making decisions related to BPR.